Student Teachers Difficulties in Teaching English to Hotel Staff - Maria Christina Eko Setyarini (Universitas Islam Negeri Walisongo Semarang, 2018)
Professional English teachers often find it difficult when they have to teach English for Specific Purpose (ESP) as they need to do extra works like doing need analysis and creating the specific syllabus before teaching to make sure that the teaching-learning process will go smoothly. Student teachers, who have less experience in teaching, are likely to face greater difficulties in teaching ESP. The study aims at finding out student teachers difficulties in teaching English to hotel staff. Therefore, eight student teachers who recently taught English to hotel staff in their teaching practicum were asked to write about their experience in teaching in form of reflections. The study reveals that the eight student teachers who taught different hotel staff in four customer related divisions, front office, housekeeping, marketing, and food and beverage face similar difficulties. The difficulties are mostly related to the hotel staff. They are teaching facilities, time management, different levels of English proficiency, and low self-efficacy. It is expected that the finding can be useful for student teachers who will do their teaching practicum in hotels, also for those who are interested in studying ESP especially in teaching English to hotel staff.Professional English teachers often find it difficult when they have to teach English for Specific Purpose (ESP) as they need to do extra works like doing need analysis and creating the specific syllabus before teaching to make sure that the teaching learning process will go smoothly. Student teachers, who have less experience in teaching, are likely to face greater difficulties in teaching ESP. The study aims at finding out student teachers difficulties in teaching English to hotel staff. Therefore, eight student teachers who recently taught English to hotel staff in their teaching practicum were asked to write about their experience in teaching in form of reflections. The study reveals that the eight student teachers who taught different hotel staff in four customer related divisions, front office, housekeeping, marketing, and food and beverage face similar difficulties. The difficulties are mostly related to the hotel staff. They are teaching facilities, time management, different levels of English proficiency, and low self-efficacy. It is expected that the finding can be useful for student teachers who will do their teaching practicum in hotels, also for those who are interested in studying ESP especially in teaching English to hotel staff.